PERLINDUNGAN HUKUM BAGI PENYANDANG DISABILITAS DI PT APPAREL ONE INDONESIA 1 - Hapsari, Herning Tyas Setyo; Saputra, Arikha (Legal Standing : Jurnal Ilmu Hukum, 2023)
Workers with Disabilities, especially those working in private companies, have rights and obligations to obtain welfare. Private companies have an obligation to employ persons with disabilities as much as 1% (one percent) of the total number of employees working in the company. As explained in Article 53 paragraph (2) of Law Number 8 of 2016 concerning Persons with Disabilities which contains "Private companies are required to employ at least 1% (one percent) of Persons with Disabilities from the total number of employees or workers". Workers with disabilities also have other rights such as obtaining employment opportunities in private companies, obtaining positions according to the type and degree of disability, obtaining health, social and other benefits, and the company is obliged to provide adequate accommodation for workers with disabilities as a form of accessibility, in accordance with what is regulated in the legislation. The research method that was carried out by the researchers used normative juridical research methods and the data used primary and secondary data. The data collection technique used in this research is the interview method for employees with disabilities and HRD PT. Apparel One Indonesia 1 has complied with statutory regulations, such as providing opportunities to work. This company has also provided health insurance, social insurance, work accidents, and others. However, accommodation and accessibility within this company are not adequate, and this company has not fulfilled the quota of workers with disabilities of 1% of the total number of employees.  for workers with disabilities without discrimination and has placed positions that are in accordance with the type and degree of disability.